Evaluation of regional sustainable development of selected Chinese provinces - Cai, Jing; Neszmélyi, György Iván; Vasa, László (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
This study aims to investigate and evaluate the status of sustainable development in the Fujian, Guangdong, and Zhejiang provinces over a decade (2011-2020) using the quantitative analysis approach of the entropy weight TOPSIS method. Based on the 12th and 13th Five-Year Plans, this research analyzes the three provinces’ social, economic, and environmental development using data collected from relevant economic and social sectors in China. The findings demonstrate that the sustainable development levels in the respective regions of these three provinces have improved, despite the impact of the COVID-19 pandemic during the study period. Drawing upon the 14th Five-Year Plan promulgated in 2021, the report provides recommendations for future social, economic, and environmental development in the examined region. The study’s results have implications for similar regions seeking to achieve sustainable development goals.